Effect of enprostil, a synthetic prostaglandin E2 on 24 hour intragastric acidity, nocturnal acid and pepsin secretion. Issue 9 (September 1986) - Deakin, M; Ramage, J; Paul, A; Gray, S P; Billings, J; Williams, J G
Abstract : We have studied the effect of a prostaglandin E2 analogue (enprostil), on intragastric acidity, gastric acid and pepsin outputs during a 24 hour period in nine patients with duodenal ulcer in remission. Enprostil 35 micrograms bd dose inhibited 24 hour intragastric acidity by 38% and a 70 micrograms nocturnal dose by 33%. Decrease in nocturnal pepsin secretion was both volume and concentration related.